From 2D leg kinematics to 3D full-body biomechanics-the past, present and future of scientific analysis of maximal instep kick in soccer - Shan Gongbing; Zhang Xiang (BMC, 2011)
Abstract Biomechanics investigation on soccer kicking has a relatively long history, yet the body of knowledge is still small. This paper reviews articles published from 1960s to 2011, summarizing relevant findings, research trends and method development. It also discusses challenges faced by the field. The main aim of the paper is to promote soccer kicking studies through discussions on problem solving in the past, method development in the present, and possible research directions for the future.